Long term precipitation trends and variability within the Mediterranean region - C. M. Philandras; P. T. Nastos; J. Kapsomenakis; K. C. Douvis; G. Tselioudis; C. S. Zerefos (Natural Hazards and Earth System Sciences, 2011)
In this study, the trends and variability of annual precipitation totals and annual rain days over land within the Mediterranean region are analyzed. Long term ground-based observations concerning, on one hand, monthly precipitation totals (1900–2010) and rain days (1965–2010) from 40 meteorological stations within the Mediterranean region were obtained from the Hellenic National Meteorological Service and the World Climate Data and Monitoring Programme (WCDMP) of the World Meteorological Organization. On the other hand, high spatial resolution (0.5° × 0.5°) gridded monthly data CRU TS 3.1 were acquired from the Climatic Research Unit, University of East Anglia, for the period 1901–2009. The two datasets were compared by means of trends and variability, while the influence of the North Atlantic Oscillation (NAO) in the Mediterranean precipitation was examined. In the process, the climatic changes in the precipitation regime between the period 1961–1990 (reference period) and the period 2071–2100 (future climate) were presented using climate model simulations (RACMO2.1/KNMI). The future climate projections were based on SRES A1B. The findings of the analysis showed that statistically significant (95% confidence level) negative trends of the annual precipitation totals exist in the majority of Mediterranean regions during the period 1901–2009, with an exception of northern Africa, southern Italy and western Iberian peninsula, where slight positive trends (not statistically significant at 95% CL) appear. Concerning the annual number of rain days, a pronounced decrease of 20 %, statistically significant (95% confidence level), appears in representative meteorological stations of east Mediterranean, while the trends are insignificant for west and central Mediterranean. Additionally, NAO index was found to be anticorrelated with the precipitation totals and the number of rain days mainly in Spain, southern France, Italy and Greece. These correlations are higher within the rain season (October–March) than the entire ...